2009
DOI: 10.1074/jbc.m109.047787
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Triglyceride Lipase Deficiency Causes Tissue-specific Changes in Insulin Signaling

Abstract: Triacylglycerol accumulation in insulin target tissues is associated with insulin resistance. Paradoxically, mice with global targeted deletion of adipose triglyceride lipase (ATGL), the ratelimiting enzyme in triacylglycerol hydrolysis, display improved glucose tolerance and insulin sensitivity despite triacylglycerol accumulation in multiple tissues. To determine the molecular mechanisms for this phenotype, ATGL-deficient (ATGL ؊/؊ ) and wild-type mice were injected with saline or insulin (10 units/ kg, intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 44 publications
9
111
0
Order By: Relevance
“…The increased fat mass in AKO/cTg mice led to a moderately higher body weight compared with WT/cTg. These findings are concordant with our earlier conclusion that defective lipolysis leads to increased adiposity in chow-fed mice (13,14).…”
Section: Significancesupporting
confidence: 83%
See 1 more Smart Citation
“…The increased fat mass in AKO/cTg mice led to a moderately higher body weight compared with WT/cTg. These findings are concordant with our earlier conclusion that defective lipolysis leads to increased adiposity in chow-fed mice (13,14).…”
Section: Significancesupporting
confidence: 83%
“…premature death but are only moderately obese (13)(14)(15). This benign adipose tissue phenotype is unexpected considering the pivotal role of ATGL in TG catabolism and led us to hypothesize that ATGL-mediated TG hydrolysis regulates lipogenesis and lipid synthesis by currently unknown mechanisms.…”
Section: Significancementioning
confidence: 99%
“…However, our results clearly show substantial increases in both DAGs and ceramides, and yet no detriments to insulin signaling. This result is at first counterintuitive; however, other reports have found similar increases in lipotoxic species without induction of insulin resistance, including the well-known athlete's paradox (31)(32)(33)(34). Elevated DAGs have been found in endurance athletes with high insulin sensitivity (35).…”
Section: Discussionmentioning
confidence: 43%
“…Although the absence of ATGL would be expected to reduce both TG hydrolysis and other lipid metabolites, DAG concentrations were, surprisingly, increased in ATGL knockout mice (30). We found that PKC was already activated before TNF␣ stimulation in ATGL knockdown HAECs (Fig.…”
Section: Discussionmentioning
confidence: 50%